Peran Digital dalam Mempermudah Transaksi Donasi di Lembaga Amil Zakat Nasional Baitul Maal Hidayatullah (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
The rapid advancement of digital technology has transformed various aspects of human life, including the field of Islamic philanthropy. Amil zakat institutions, as organizations responsible for collecting and distributing zakat, are required to adapt to these changes to ensure efficiency, transparency, and accessibility in their services. This study aims to describe how digitalization supports and facilitates the donation transaction process at the National Amil Zakat Institution Baitul Maal Hidayatullah (BMH). Employing a qualitative descriptive method with a case study approach, data were collected through direct observation, document analysis, and informal interviews with amil staff as well as donors. The findings show that the integration of digital media—such as WhatsApp Broadcast for information dissemination, Google Forms for donor data collection, bank transfers and QRIS-based payment systems for financial transactions, and social media platforms for outreach—significantly simplifies the donation process. Through these digital tools, donors are no longer constrained by geographical distance, limited time, or complex manual procedures. Moreover, the amil team’s fast responses via digital communication channels enhance donor trust, satisfaction, and loyalty. Nevertheless, the study also identifies several challenges, including risks of number blocking on messaging platforms, limited digital literacy among certain donor segments, and potential concerns regarding system security and credibility. To overcome these challenges, BMH applies a human-centered communication strategy, system innovation, and continuous adaptation to technological changes. Overall, the study concludes that digitalization plays a vital role in accelerating, simplifying, and expanding the scope of zakat donation transactions. It not only supports the sustainability of BMH’s humanitarian and da’wah programs but also demonstrates how digital transformation can strengthen Islamic philanthropy institutions in the digital era.